1984
DOI: 10.1007/bf00275660
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in lymphocyte subpopulations in type 1 (insulin-dependent) diabetes mellitus: exploration of possible mechanisms and relationships to autoimmune phenomena

Abstract: Previous studies have shown a variety of immunological abnormalities in Type 1 (insulin-dependent) diabetes, including disturbances in peripheral lymphocytes and anti-lymphocyte antibodies. We measured subsets of T and natural killer cells with monoclonal antibodies in patients with diabetes, and also assayed for anti-lymphocyte antibodies using dual colour immunofluorescence and flow cytometry. We found a significant decrease in numbers of Leu 3a (helper/inducer) cells in Type 1 diabetic patients of recent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 16 publications
0
33
1
Order By: Relevance
“…The lymphocyte ratio, despite its poor specificity, is a simple and widely used test for evaluation of the cell mediated immune response [16] and is reported to be reduced in patients with a long duration of disease [3,4]. Immunoregulatory lymphocyte subsets have a major role in the induction of a primary immune response (as in the case of the B hepatitis vaccine) and any abnormality of these cells in number and/or function may result in impaired generation of a specific cell mediated and humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lymphocyte ratio, despite its poor specificity, is a simple and widely used test for evaluation of the cell mediated immune response [16] and is reported to be reduced in patients with a long duration of disease [3,4]. Immunoregulatory lymphocyte subsets have a major role in the induction of a primary immune response (as in the case of the B hepatitis vaccine) and any abnormality of these cells in number and/or function may result in impaired generation of a specific cell mediated and humoral immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The number of circulating helper (CD4) cells is reduced [2], the helper/suppressor (CD4/CD8) lymphocyte ratio is decreased [3,4], phagocytic activity is impaired [5] and lymphocyte blastogenesis is reduced [6]. These are amongst the most consistent alterations reported in vitro and may well account for the greater susceptibility to infection in patients with poor metabolic control [7].…”
mentioning
confidence: 99%
“…Increased NK cell activity has been reported in the periphery of individuals with type 1 diabetes [1][2][3][4][5][6], but a role for these innate immune cells in the pathogenesis of type 1 diabetes has not, however, been elucidated. NK cells act by either activating or inhibiting cytolysis [7] and their activity is controlled by the balance of inhibitory and activating receptors on the cell surface [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the first ground-breaking studies, decreased CD4/CD8 lymphocyte ratios, reduced lymphocyte blastogenesis, and acquired defects in interleukin-2 production were observed in people affected by DM (1,2,3). Subsequent research revealed reduced T-cell primary responses to protein antigens (4).…”
mentioning
confidence: 99%